The impact of artificial intelligence on the Greek economy - Constantinos Challoumis; Nikolaos Eriotis (Journal of Open Innovation: Technology, Market and Complexity, 2025)
This study examines the impact of Artificial Intelligence (AI) on the Greek economy, assessing its effects on economic growth, employment, productivity, and sectoral competitiveness. The research aims to provide a comprehensive evaluation of AI adoption, its potential benefits, challenges, and policy implications in the Greek economic context. The study employs a multisector dynamic general equilibrium model calibrated using input-output data from 2015–2021. The model simulates AI-induced capital stock accumulation and Total Factor Productivity (TFP) growth, focusing on sectoral shifts and macroeconomic outcomes. The research integrates quantitative modeling with qualitative analysis, leveraging existing economic literature and policy frameworks to contextualize AI’s role in economic transformation. The study covers key sectors of the Greek economy, including manufacturing, services, public administration, and technology-intensive industries. It also addresses the interplay between AI adoption, labor market changes, and policy interventions, comparing Greece's AI readiness with broader European and global trends. Findings suggest that AI adoption can significantly enhance productivity and economic efficiency. The assumption is based on certain assumptions to comply with the initial hypothesis; meaning that if these assumptions are not followed the results will have a divergence. In any case, a baseline is made to be able to study and different conditions of the model. However, slow adoption, structural economic weaknesses, and labor displacement pose major challenges. Government initiatives and private sector investments are critical in accelerating AI integration while mitigating adverse socio-economic impacts.